Środowiskowe i międzypokoleniowe działania animacyjne Koła Naukowego Anim@cja = Environmental and intergenerational animation activities by Anim@cja scientific circle - Wilkowska, Agnieszka; Dąbrowska, Kornelia; Olejarz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article focuses on the environmental and intergenerational activities of the Anim@cja scientific circle, which despite its short history (it was founded in November 2021), showed many animation initiatives. The authors, referring to the literature of the subject, pointed to the tasks of scientific circles as increasingly popular student organizations, whose role for the individual development of students as well as cooperation with the local community is particularly valuable and significant. They also presented the genesis of the Anim@cja scientific circle at the Faculty of Social Sciences at the University of Zielona Góra, as well as its main ideas and statutory tasks.
Keywords: koło naukowe; animacja kulturalna; projekt animacyjny; środowisko lokalne; działania międzypokoleniowe; seniorzy; studenci; scientific circle; cultural animation; animation project; local environment; intergenerational activities; seniors; students